2007
DOI: 10.1021/es071217x
|View full text |Cite
|
Sign up to set email alerts
|

Microbially Derived Inputs to Soil Organic Matter: Are Current Estimates Too Low?

Abstract: Soil microbes are central to many soil processes, but due to the structural complexity of soil organic matter, the accurate quantification of microbial biomass contributions continues to pose a significant analytical challenge. In this study, microbes from a range of soils were cultured such that their molecular profile could be compared to that of soil organic matter and native vegetation. With the use of modern NMR spectroscopy, the contributions from microbial species can be discerned in soil organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
298
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 450 publications
(312 citation statements)
references
References 29 publications
14
298
0
Order By: Relevance
“…The importance of microbial residues for soil carbon storage is suggested to even increase over time 23 . Thus, in line with the recent debate [42][43][44] , our findings challenge previous views underestimating or even negating the influence of size and activity of soil microorganisms on soil carbon storage.…”
supporting
confidence: 89%
“…The importance of microbial residues for soil carbon storage is suggested to even increase over time 23 . Thus, in line with the recent debate [42][43][44] , our findings challenge previous views underestimating or even negating the influence of size and activity of soil microorganisms on soil carbon storage.…”
supporting
confidence: 89%
“…SOM models that include microbial community structure have shown that changes in microbial physiology, often expressed as CUE (defined as the amount of C in microbial biomass relative to C respired and in biomass), have the potential to dramatically impact the fate of C stocks to climate change (Allison et al, 2010;Schimel, 2013;Wieder et al, 2013;Li et al, 2014), and experimental evidence shows that CUE can be altered by substrate quality, temperature, and N availability (Dijkstra et al, 2011;Manzoni et al, 2012;Frey et al, 2013;Tucker et al, 2013). This concept of changes to CUE is of particular importance as a large portion of SOM has been attributed to microbial derived products, which may have a relatively long turnover time (Simpson et al, 2007;Liang and Balser, 2008;Miltner et al, 2012;Gleixner, 2013). It is therefore necessary to determine the underlying mechanisms and the extent that microbial community structure and function impacts C turnover in response to these global change scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The 1 H-13 C heteronuclear Single Quantum Coherence (HSQC) spectrum (Fig. 4a) clearly identifies the majority of peaks to be consistent with protein 26,27 . This is particularly evident for the protein a-C-H region (3.4-4.5 p.p.m.)…”
Section: Resultsmentioning
confidence: 97%